2014
DOI: 10.1159/000360992
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Disparities among Ethnic Subgroups of Waldenström's Macroglobulinemia: A Population-Based Study

Abstract: Background: Ethnic disparities in cancers are associated with variability in clinical outcomes. We present a Surveillance Epidemiology and End Results (SEER)-based outcome analysis of multiethnic Waldenström's macroglobulinemia (WM) patients. Methods: Adult WM patients diagnosed in 1992 or later (n = 3,175) were analyzed. Median overall survival (OS) was compared across different ethnicities stratified by year of diagnosis, registry identification, age at diagnosis, sex, and marital status. Results: African-Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Two recent studies have evaluated outcomes in patients with WM using the SEER database (Sekhar et al , ; Ailawadhi et al , ). Both of these studies analysed a significantly smaller sample than our study, including only patients with WM (ICD‐9 code 9761).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have evaluated outcomes in patients with WM using the SEER database (Sekhar et al , ; Ailawadhi et al , ). Both of these studies analysed a significantly smaller sample than our study, including only patients with WM (ICD‐9 code 9761).…”
Section: Discussionmentioning
confidence: 99%
“…Black patients less commonly have IgM monoclonal gammopathy compared with white patients . Median age at diagnosis is 63 years for blacks and 73 for whites . The presence of the monoclonal IgM protein adds a unique dimension to the disorder because it can result in hyperviscosity syndrome , peripheral neuropathy , hemolytic anemia , and immune complex vasculitis .…”
Section: Disease Overviewmentioning
confidence: 99%
“…Subsequent research confirmed a familial predisposition, as well as elevated risk for secondary malignancies in this disease [10,11]. Recent studies suggested better survival [12][13][14] but could not discern whether this was due to earlier diagnosis (lead-time bias) or therapeutic advances. To our knowledge, no reports described use of health services or prevalence of WM-related complications using populationbased data.…”
Section: Introductionmentioning
confidence: 99%